TRADISI PEMBELAJARAN DAN TELAAH PENDIDIKAN PADA MASA DAULAH BANī ABBĀSIYAH - Ali Rahmat (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2017)
History has noted that the age of Daulah ‘Abbāsiyah was the golden age of Islam especially in the field of education. Various branches have grown at this time, coupled with many book translators from foreign language to Arabic. This article discussed the learning tradition existed in the Banī ‘Abbāsiyah era. Further, the detail of how the learning goes on will be discussed in this article in order to make us know ins and outs of science’s development at that time and can be used as the pillar of science’s development in this era.Key words: Learning, History, Banī ‘Abbāsiyah